Optimization of biofunctional jaggery yogurt: It’s physicochemical and antioxidant properties - Tripathi, Abhishek Dutt; Kumar, Pankaj; Agarwal, Aparna (Indian Journal of Dairy Science, 2022)
In addition to the standard healthy diet needs, balance food is taught to be a healthier diet that will promote human health. It’s also known as functional food, which is food that clearly claims to have health advantages as well as the ability to enhance the immune system. Yoghurt is a fermented dairy product that is in great demand for its nutrient content, bacterial activity and wide product range in terms of flavours and textures. In this study, physicochemical, microbiological and sensory differences of probiotic set yoghurt incorporated with different concentration of Jaggery were evaluated, as well as the changes taking place during storage at 4°C for 21 days. During the storage, the addition of jaggery improved survival of Lactobacillus delbrueckii subspecies bulgaricus (ABT-7) and Streptococcus thermophiles (YoFlex Express 1.0) from CHR HANSEN, Denmark were used as starter culture for yogurt preparation. All yogurts exhibited a decrease in pH accompanied by an increase in titratable acidity during storage. Therefore, this study revealed that jaggery could be used to produce probiotic set yoghurt with improved physicochemical, microbiological and sensorial attributes.